Three essays on finance - Yang, Chuyi (Nanyang Technological University, 2020)
In Chapter 1, using large lottery jackpots on Saturday as repeated exogenous shocks to investor attention, we find that the Monday effect of market return and the Monday effect of anomalies only exist on Mondays with a large jackpot on the preceding Saturday. For example, the Monday effect of high idiosyncratic volatility stocks is a striking - 64 bps when there was a large Saturday jackpot but is negligible otherwise. This is consistent with the hypothesis that individual investors allocate the weekends to process information and decide on trading strategies. Large jackpots during the weekends distract individual investors’ attention from the stock market, resulting in less buying relative to selling, lower return and larger stock co-movement on the following Monday. The jackpot effect is larger among stocks preferred by individual investors. Interestingly, we do not find similar jackpot effect on weekday drawings. In Chapter 2, we study the real effects of foreign exchange hedging on corporate innovation. Under the information asymmetry hypothesis, corporate hedging reduces firm’s information asymmetry, and alleviates manager’s career concern from undervaluation and helps investors to better monitor the manager, which in turn increases innovation. Under the market pressure hypothesis, hedging imposes more short-term earnings pressure on managers because of mark-to-market hedge accounting, hence leads to lower innovation. Our results support the information asymmetry hypothesis. Hedged firms invest more heavily in innovative projects, generate more patents and have more patent citations. To address endogeneity concerns, we employ both difference-in-differences and instrumental variables regressions, and test for reverse causality explicitly. In Chapter 3, we document a measure of law firm expertise that could predict the outcomes of future lawsuits conducted by the law firm, using securities class action lawsuits from 1996 to 2013. We use prior Dismissed Ratio as law firm expertise measure on a rolling basis, defined as ratio of number of dismissed cases to number of total cases conducted by the law firm in the past 5 years. It is found that law firms with lower prior Dismissed Ratio are more likely to be skilled law firms with less agency problem. Cases conducted by skilled law firms with less agency problem are more likely to be settled, have more negative cumulative abnormal return during the filing date, win larger settlement amount, result in larger probability of CEO turnover and are associated with larger short interest one week prior to the filing event. Skilled law firms contribute to better outcomes by exerting more effort in the litigation process, as evident by the longer Case Length from filing date to status date. In addition, market share of law firms increases after performing as skilled law firms and skilled law firms are less likely to disappear from the market in the future. Overall, predictive power and persistence of law firm expertise suggest law firm fixed effect in securities class action lawsuits. Robustness tests suggest existence of law firm expertise beyond case selection.